Genetic vulnerability to schizophrenia is associated with cannabis use patterns during adolescence. (1st September 2018) - Hiemstra, Marieke; Nelemans, Stefanie A.; Branje, Susan; van Eijk, Kristel R.; Hottenga, Jouke-Jan; Vinkers, Christiaan H.; van Lier, Pol; Meeus, Wim; Boks, Marco P.
Highlights: Evidence of a genetic overlap between schizophrenia (SCZ) and cannabis use pattern over time. Lenient PRS thresholds for schizophrenia were associated with delayed cannabis use. Stringent PRS thresholds were associated with a stronger increase in cannabis use. No evidence for a genetic overlap between SCZ, alcohol, and smoking pattern over time. Abstract: Background: Previously reported comorbidity between schizophrenia and substance use may be explained by shared underlying risk factors, such as genetic background. The aim of the present longitudinal study was to investigate how a genetic predisposition to schizophrenia was associated with patterns of substance use (cannabis use, smoking, alcohol use) during adolescence (comparing ages 13–16 with 16–20 years). Method: Using piecewise latent growth curve modelling in a longitudinal adolescent cohort (RADAR-Y study, N  = 372), we analyzed the association of polygenic risk scores for schizophrenia (PRS; p-value thresholds ( pt )  < 5e-8 to pt   < 0.5) with increase in substance use over the years, including stratified analyses for gender. Significance thresholds were set to adjust for multiple testing using Bonferroni at p  ≤ 0.001. Results: High schizophrenia vulnerability was associated with a stronger increase in cannabis use at age 16–20 (PRS thresholds pt  <  5e-5 and pt   < 5e-4; pt  <  5e-6 was marginally significant), whereas more lenient PRS thresholds (PRS thresholds pt   < 5e-3 to pt   < 0.5) showed the reverse association. For smoking and alcohol, no clear relations were found. Conclusions: In conclusion, our findings support a relation between genetic risk to schizophrenia and prospective cannabis use patterns during adolescence. In contrast, no relation between alcohol and smoking was established.